CSIR-CRI and PPRSD Training for Esoko Call Center Operatives - Kyeremeh, Emmanuel Margo; Koi, Gordon Nii (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The paper highlights the outcomes of capacity development training activities organised by AICCRA in collaboration with Crops Research Institute of the Council for Scientific and Industrial Research and the Plant Protection and Regulartory Services Directorate of the Ministry of Food and Agriculture to support call centre staff of Esoko to provide accurate and timely information on Climate Smart Agriculture technologies, practices and associated advisories to farmers.